Mathematical Proof – Argumentation or Derivation? – Part I - Wójtowicz, Krzysztof (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2011)
The article is devoted to the problem of status of mathematical proofs, in particular it tries to capture the relationship between the real, „semantic” notion of mathematical proof, and its formal (algorithmic) counterpart. In the first part, Azzouni’s derivation–indicator view is presented in a detailed way. According to the DI view, there is a formal derivation underlying every real proof.